Voltage Control of Grid-Connected PV System Facing Voltage Sags - Le, Duc Tung; Le, Thi Minh Chau (Old Journal, 2020)
There is an exponential growth of implementation of renewable energy generation systems in recent years. The photovoltaic system (PV system) takes an important place due to its simple integration to the grid. However, a disturbance in the grid could have a significant impact on PV system operation. Voltage sags are acknowledged to be one of the major power quality disturbances which can provoke the PV system disconnection due to the decoupling protection. With a less severe voltage sags, for example in case of a momentary faults or short circuits on the adjacent feeder, this disconnection is not desired. This results to the essential need of the development a voltage control at the connection point. This article presents the development an auto adaptative voltage control integrated into the PV inverters. Facing the voltage sags, this control system allows the voltage at the connection point greater than an admissible voltage threshold of decoupling protection, the connection of PV system is so maintained. The models and simulations are developed in Matlab-Simulink. The obtained results are satisfied.